Development and Implementation of Interprofessional Relations Between a College of Pharmacy and Osteopathic Residency Programs in a Community Teaching Hospital. (February 2020) - Boylan, Paul M.; Sedlacek, Jordan; Santibañez, Melissa; Church, Andria F.; Lounsbury, Nicole; Nguyen, Jacqueline
Background: Team-based health care optimizes patient outcomes, and therefore, both interprofessional education (IPE) and interprofessional relations (IPR) are required in health professions education, postgraduate training, and real-world clinical practice. Existing literature describes progressive developments and assessments of IPE in colleges of pharmacy and medicine; however, there are fewer reports describing processes or projects that foster physician-pharmacist IPR in clinical practices without established interprofessional collaborations.Objectives: The primary objective was to establish IPR between pharmacists and osteopathic residents in a community teaching hospital. The secondary objective was to innovate the delivery of pharmacotherapeutic content delivered to the residents during their didactic lecture series by providing active learning strategies.Methods: This report describes a project wherein college of pharmacy faculty developed IPR with osteopathic residents in a community teaching hospital that previously did not have any established physician-pharmacist IPR. Osteopathic medical residents completed a post-implementation survey after they attended a 12-month series of didactic lectures that incorporated active learning delivered by pharmacist faculty.Results: Sixty-six residents were eligible to complete the survey; 20 residents completed the survey. Eighteen residents believed that both physicians and pharmacists should be educated to establish IPR and that it should be included in professional, graduate, and continuing education settings for both professions. Sixteen residents believed that the active learning techniques employed by college of pharmacy faculty were useful for IPR.Conclusions: Physician-pharmacist IPR may be achievable in settings where IPR was previously sparse. Shared interests, adherence, and innovations in IPR frameworks are essential for developing physician-pharmacist IPR.